1978
DOI: 10.1055/s-0028-1091493
|View full text |Cite
|
Sign up to set email alerts
|

Metachromatic Leukodystrophy: A Comparative Study of the Ultrastructural Findings in the Peripheral Nervous System of Three Cases, One of the Late Infantile, One of the Juvenile and one of the Adult Form of the Disease

Abstract: The ultrastructural findings in the peripheral nerve of three cases of M. L. D., namely of the late infantile, the juvenile and the adult form are described. The pathological changes consist of two phenomena: segmental demyelination and lysosomal storage of sulfatides, both probably separate results of a deficiency of the enzyme Arylsulfatase A. Some differences are found in the degree of segmental demyelination and the type of lysosomal storage products. A possible relation between these differences and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Histopathologic evaluation of nerve biopsy specimens has been an important diagnostic tool for MLD patients in the past, but can also enhance our understanding of disease pathogenesis nowadays. An overview of the published peripheral nerve abnormalities in different MLD studies is presented in (Additional file 3: Table S2) [5, 31, 42-46, 53, 55-63].…”
Section: Neuropathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathologic evaluation of nerve biopsy specimens has been an important diagnostic tool for MLD patients in the past, but can also enhance our understanding of disease pathogenesis nowadays. An overview of the published peripheral nerve abnormalities in different MLD studies is presented in (Additional file 3: Table S2) [5, 31, 42-46, 53, 55-63].…”
Section: Neuropathologymentioning
confidence: 99%
“…Besides, some studies found that tuffstone bodies are more frequent in late-infantile MLD, while zebra bodies are more frequent in juvenile and adult MLD. However, whether different inclusion body types have different roles in disease pathogenesis is unclear as different types can blend into each other and most likely reflect different orientations and packing of metachromatic material instead of different disease mechanisms [5, 56].…”
Section: Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation
“…There are 3 main clinical types of MLD which are as follows: late-infantile (age of onset before 30 months), juvenile (age of onset between 2.5 and 16 years), and adult onset (age of onset after 16 years) [6] . The type and severity of the symptoms of MLD correlate with the levels of residual ASA activity [ 4 , 5 ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…MLD is named from the presence of metachromatic granules in the affected cells, formed as a result of the accumulation of sulfatide and sphingolipids in myelin [3] . The type and severity of the symptoms of MLD correlate with the levels of residual ASA activity [ 4 , 5 ]. There are 3 main clinical types of MLD which are as follows: late-infantile (age of onset before 30 months), juvenile (age of onset between 2.5 and 16 years), and adult-onset (age of onset after 16 years) [6] .…”
Section: Introduction and Importancementioning
confidence: 99%